UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK DI SMA ISLAM SUDIRMAN AMBARAWA TAHUN AJARAN 2023/2024 - Ningsih, Rista Arin; Tagela, Umbu; Maria, Adhi Krisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the efforts of guidance and counseling teachers in improving student skills at Sudirman Ambarawa Islamic High School in the 2023/2024 school year. This research uses qualitative research methods. This type of research is descriptive. The data collection techniques used are interviews, observation, and documentation. The data were analyzed by data reduction, data presentation, and conclusion drawing. The subjects or informants in this study are counseling teachers and students who have low social skills. This study identified several findings related to the efforts made by counseling teachers in improving students' social skills. These efforts include: BK teachers provide a series of understandings about socializing which are carried out classically and provide ice breaking aimed at knowing the enthusiasm in interacting between students and their peers, BK teachers provide opportunities for students to respond well in play groups with their peers, BK teachers provide BK instruments and process the results obtained to determine the number of students with social problems, BK teachers provide BK services such as individual counseling with a reality counseling approach, BK teachers provide group guidance role-playing techniques and provide group counseling according to the number of students experiencing social skills problems.